Synthesis, structure and electrochemical performance of the argyrodite Li6PS5Cl solid electrolyte for Li-ion solid state batteries. (10th October 2016) - Yu, Chuang; van Eijck, Lambert; Ganapathy, Swapna; Wagemaker, Marnix
Abstract: The high lithium conductivity of argyrodite Li6 PS5 Cl makes it an attractive candidate as solid electrolyte in all solid-state Li batteries. Aiming at an optimal preparation strategy the structure and conductivity upon different mechanical milling times is investigated. Li6 PS5 Cl material with high ionic conductivity of 1.1·10 −3 S/cm was obtained by milling for 8 hours at 550 rpm followed by a heat-treatment at 550 °C. All solid-state Li-S batteries were assembled, combining the Li6 PS5 Cl solid electrolyte, with a carbon-sulfur mixture as positive electrode and Li, Li-Al and Li-In as negative electrode. An optimum charge/discharge voltage window between 0.4 and 3.0 V vs. Li-In was obtained by CV experiments and galvanostatic cycling displays a very large capacity around 1400 mAh/g during the first cycles, decreasing below 400 mAh/g after 20 cycles. Impedance spectroscopy suggests that the origin of the capacity fading is related to an increasing electrode-electrolyte interface resistance.